Evaluasi Kondisi Lingkungan Akuakultur Pada DAS Tondano Di Kelurahan Ternate Baru Kota Manado - Wakman, Dolvinus; Undap, Suzanne L; Salindeho, Indra (e-Journal BUDIDAYA PERAIRAN, 2015)
In this study, we evaluated the current condition of the environmental conditions of aquaculture on watershed Tondano River in terms of physical and chemical parameters. Determination of sampling points at each station is placed vertically at three predetermined points from the brigde toward the front of the aquaculture, the distance between one point to the next point was Â± 50 m; whereas for the analysis of water quality parameters was done using an HORIBA water quality meters type U-536. Determination points were done by purposive sampling which refers to the physiographic location wherever possible in order to represent or describe these waters. The research was carried out for 3 weeks and was done in 3 stages, morning, afternoon and evening. For direct measurement (in situ) was performed once a week at the three points which included parameters pH, temperature, conductivity, DO, Oxidation reduction potential, turbidity, TDS, depth and GPS. Generally, the result of water quality analysis at the aquaculture still in the water quality standard PP No.82 of 2001. Keywords: Evaluation, water quality, water Lake Tondano, Aquaculture